2013
DOI: 10.1370/afm.1446
|View full text |Cite
|
Sign up to set email alerts
|

Participants' Explanatory Model of Being Overweight and Their Experiences of 2 Weight Loss Interventions

Abstract: PURPOSEWe explored participants' accounts of weight loss interventions to illuminate the reasons behind the greater weight loss observed among those attending a commercial program compared with those receiving standard care in a recent large-scale trial. We further wanted to examine how participants' general explanatory model of being overweight related to the 2 different interventions. METHODSOur study was based on thematic analysis of semistructured telephone interviews with a purposeful sample of 16 female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 16 publications
2
52
0
Order By: Relevance
“…We identified 21 studies reported in 26 papers that reported service‐user views on WMPs (see Figure for PRISMA figure presenting flow of studies through the review). The 21 studies reported the views of 507 service users, and there was a good range in terms of gender, age and socio‐economic status, but limited data from minority‐ethnic service users; just one study focused on a programme specifically for a minority‐ethnic group and most others which provided information on the ethnicity of participants stated that they were predominantly white British.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 21 studies reported in 26 papers that reported service‐user views on WMPs (see Figure for PRISMA figure presenting flow of studies through the review). The 21 studies reported the views of 507 service users, and there was a good range in terms of gender, age and socio‐economic status, but limited data from minority‐ethnic service users; just one study focused on a programme specifically for a minority‐ethnic group and most others which provided information on the ethnicity of participants stated that they were predominantly white British.…”
Section: Resultsmentioning
confidence: 99%
“…Service users in about half of the studies discussed dietary (n = 12 studies) and exercise (n = 11 studies) features of WMPs, and views on these programme aspects were divergent with respect to perceived relevance and utility. For example, whilst 9 studies included positive service‐user statements about the focus of WMPs on diet, participants in 7 studies indicated a perceived lack of need for dietary advice, for instance:
Perhaps counter to public health assumptions, none of the participants talked about needing an intervention to include education about food, eating, or diet as they believed they already had the necessary knowledge.
…”
Section: Resultsmentioning
confidence: 99%
“…We ensured that patients who agreed to referral left the practice with an appointment. Finally, we drew on evidence that external accountability is an important component of behavioural programmes 23 and we trained physicians to ask the participant to return in 4 weeks to assess their progress (panel). …”
Section: Methodsmentioning
confidence: 99%
“…14 Findings from a study of explanatory models of people attending primary care or commercial weight loss programs have implications for tailored interventions that balance patients' valuation of motivation, education, and group vs individual support. 15 In a cohort study featured in Annals Journal Club, Lisman-van Leeuwen and colleagues fi nd a surprisingly high prevalence and long duration of chronic abdominal pain among children complaining of abdominal pain in primary care. 16 A study of presentations at the Society of Teachers of Family Medicine and the North American Primary Care Research Group fi nds that a surprising (to me at least) number or presentations become publications, and (not surprisingly) appear in a wide variety of journals.…”
Section: Other Interesting Research In This Issuementioning
confidence: 99%